Optical Back-Propagation for Nonlinear Compensation in OFDM-Based Long Range-Passive Optical Networks - Ngo, Thi Thu Trang (H. : ĐHQGHN, 2020)
In direct-detection optical OFDM system, the nonlinear impairment is the key factor that limits the system performance. The back-propagation techniques in digital and optical domains have been proposed to compensate the nonlinear effects, however they can be unsuitable for long-range passive optical networks (LR-PONs) due to their implementation at receiver. In this study, we propose an optical back propagation (OBP) approach for compensation of the nonlinear and dispersion distortions in direct-detection optical OFDM system. The proposed OBP using split-step Fourier method is implemented at transmitter that is suitable for high-rate OFDM-based LR-PONs applications. In this OBP, the fiber Bragg grating (FBG) is used as a step for dispersion compensation and the high-nonlinear fiber (HNLF) with a short length is used as a step for nonlinear compensation. The performance improvement based on our proposed approach has been demonstrated via Monte-Carlo simulations of the 100 Gbit/s direct-detection optical OFDM system with 80 km of standard single mode fiber link. The influence of optical conjugation process and launching conditions has been investigated. The obtained results show that the proposed OBP can improve remarkably the performance of system with the launched power range from -2 dBm to 6 dBm.